Clonal Spread of Salmonella enterica Serovar Infantis in Serbia: Acquisition of Mutations in the Topoisomerase Genes gyrA and parC Leads to Increased Resistance to Fluoroquinolones. (11th October 2013) - Velhner, M.; Kozoderović, G.; Grego, E.; Galić, N.; Stojanov, I.; Jelesić, Z.; Kehrenberg, C.
Summary Quinolone‐resistant Salmonella Infantis (n = 64) isolated from human stool samples, food and poultry during the years 2006–2011 were analysed for their resistance phenotypes, macrorestriction patterns and molecular mechanisms of decreased susceptibility to fluoroquinolones. Minimum inhibitory concentrations (MICs) of nalidixic acid (NAL) and ciprofloxacin (CIP) were determined by the agar dilution procedure, and the susceptibility to additional antimicrobial agents was determined by the disc diffusion method. To assess the influence of enhanced efflux activity, MICs were determined in the presence and absence of the inhibitor PAβN. The results of pulsed‐field gel electrophoresis (PFGE) typing revealed that quinolone‐resistant S. Infantis in Serbia had similar or indistinguishable PFGE profiles, suggesting a clonal spread. All S. Infantis showed combined resistance to NAL and tetracycline, whereas multiple drug resistance to three or more antibiotic classes was rare (2 isolates of human origin). The MICs ranged between 512 and 1024 μg/mL for NAL and 0.125–2 μg/mL for CIP. A single‐point mutation in the gene gyrA leading to a Ser83→Tyr exchange was detected in all isolates, and a second exchange (Ser80→Arg) in the gene parC was only present in eight S. Infantis isolates exhibiting slightly higher MICs of CIP (2 μg/mL). The inhibitor PAβN decreased the MIC values of CIP by two dilution steps and of NAL by at minimum 3–6 dilution steps, indicating that enhanced efflux plays an important role in quinolone resistance in these isolates. The plasmid‐mediated genes qnr, aac(6′)‐lb‐cr and qepA were not detected by PCR assays.